2017
DOI: 10.1017/s1751731116002056
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary grape proanthocyanidins on the growth performance, jejunum morphology and plasma biochemical indices of broiler chicks

Abstract: Grape proanthocyanidins (GPCs) are a family of naturally derived polyphenols that have aroused interest in the poultry industry due to their versatile role in animal health. This study was conducted to investigate the potential benefits and appropriate dosages of GPCs on growth performance, jejunum morphology, plasma antioxidant capacity and the biochemical indices of broiler chicks. A total of 280 newly hatched male Cobb 500 broiler chicks were randomly allocated into four treatments of seven replicates each,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
9
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 45 publications
5
9
1
Order By: Relevance
“…In contrast, 6% dietary inclusion of a GP concentrate did not modify performance or diet digestibility but showed antioxidant potential that was as effective as vitamin E in diet, excreta, ileal content, and breast muscle [15]. Other authors evidenced that the dietary supplementation of grape byproducts increased activity of total superoxide dismutase and decreased the content of malondialdehyde in plasma [19] and leg meat [55], whereas this was not observed in the present study when measuring meat TBARs.…”
Section: Discussioncontrasting
confidence: 94%
See 2 more Smart Citations
“…In contrast, 6% dietary inclusion of a GP concentrate did not modify performance or diet digestibility but showed antioxidant potential that was as effective as vitamin E in diet, excreta, ileal content, and breast muscle [15]. Other authors evidenced that the dietary supplementation of grape byproducts increased activity of total superoxide dismutase and decreased the content of malondialdehyde in plasma [19] and leg meat [55], whereas this was not observed in the present study when measuring meat TBARs.…”
Section: Discussioncontrasting
confidence: 94%
“…Notably, most of the differences in favor of GP supplementation regarding the overall transcriptomic response appeared in the second period of growth. Overall, this is consistent with the results of Farahat et al [ 73 ] and Yang et al [ 19 ], who observed a time-dependent cumulative effect of dietary supplementation with grape seed extracts and pomace concentrate. However, according to some authors [ 8 , 53 ], the dietary supplementation with tannins (from grape seed and CN extracts) was more effective in younger broilers than in older ones, likely based on their effects on pathogenic microorganisms as well as on commensal microbiota [ 74 , 75 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In a study, Viveros et al [15] reported that poly-phenol-rich grapes enhanced villus dimensions in 21 day-old broiler chickens. Similar to our study, Yang et al [20] suggested that grape proanthocyanidin at the rate of 7.5 and 15 mg/kg improved the jejunum morphology in broilers. Bagchi et al [21] suggested that proanthocyanidin protects the intestinal mucosa from oxidative stress and inhibits pathogenic intestinal microflora, leading to healthy intestines.…”
Section: Discussionsupporting
confidence: 91%
“…The small intestinal absorptive surface is known to be either positively or negatively affected by various factors: including the environment (Santos et al, 2015; Zhang et al, 2015), feed supplements from various sources (Xu et al, 2003; Laudadio et al, 2012; Yang et al, 2017) pathogenic microbiota and mycotoxin feed contaminants (Jayaraman et al, 2013; Yu et al, 2018). It is already known to be altered by different nutritional conditions (Yamauchi, Kamisoyama & Isshiki, 1996; Bhanja et al, 2009).…”
Section: Introductionmentioning
confidence: 99%